Keanekaragaman Makrozoobentos di Perairan Danau Kelubi Kecamatan Tayan Hilir Kabupaten Sanggau - Ari Hepi Yanti, Rusmiati, Tri Rima Setyawati (Jurnal Protobiont, 2014)
Kelubi lake has an area of ?? 220 ha and high puddles influenced by rainfall. The research aimed to know macrozoobenthos diversity and the quality of Kelubi lake waters. Determination of five sampling stations based on different environmental setting. Macrozoobenthos samples were taken three times at each station by Ekman Grab and identified in the Zoology Laboratory of the Faculty of Mathematics and Natural Sciences of Tanjungpura University Pontianak. Macrozoobenthos research results obtained in the waters of Lake Kelubi four genera namely Chironomus, Dasyhelea, Dixella and Limnodrilus. Value abundance of macrozoobenthos in Lake Kelubi ranged from 44.44 to 355.55 Ind/m2. The diversity index (H) of the highest macrozoobenthos obtained at station IV of 355.55 Ind/m2 and lowest at station I of 0.5004 Ind/m2. The macrozoobenthos diversity in Kelubi lake was low to moderate. The average of evenness index (E) of macrozoobenthos was 0.8650 which indicates high evenness, while the average of Simpson dominance index (C) wason the average of 0,4950 which in considered low dominance of macrozoobenthos. The result of Pearson correlation test shows that depth, temperature, transparency, organic substrate significantly affect the diversity of macrozoobenthos in Kelubi lake. Kelubi lakes classified in moderate pollution levels.